Analisis Perilaku Konsumen terhadap Keputusan Pembelian E-commerce Shopee selama pandemi Covid-19 - Sari, Yovita; Yohana Helena (International Journal Administration, Business & Organization, 2021)
As technology develops today, human life is made easier. During the Pandemic era that was hitting the world, technology played an important role in people's lives. The influence of the pandemic has also changed people's lifestyles, such as changes in consumer behavior who now prefer to use E-Commerce during the Pandemic. With E-Commerce, the process of business transactions is easier, more practical and safer.